2018
DOI: 10.1002/aur.1957
|View full text |Cite
|
Sign up to set email alerts
|

Happiness, self‐esteem, and prosociality in children with and without autism spectrum disorder: Evidence from a UK population cohort study

Abstract: High levels of childhood happiness, self-esteem, and prosociality are associated with positive social and emotional outcomes. In this study, we investigated whether happiness, self-esteem and prosociality co-occur in children, and how possible co-occurrence differs between those with and without Autism Spectrum Disorder. We found that for the majority of children happiness, self-esteem, and prosociality co-occur. Furthermore, although as a group children with ASD have lower levels of positive functioning, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 71 publications
2
11
0
1
Order By: Relevance
“…For the second stage of the mediation model (self-esteem→pro-social tendency), self-esteem was positively associated with pro-social tendencies in LBAs. This finding is congruent with previous research (Zuffiano et al, 2016; Fu et al, 2017; McChesney and Toseeb, 2018), indicating that people with high self-esteem are more likely to have high pro-social tendency. This finding supports the notion that self-esteem is a motivating factor and important psychological resource for achieving positive social outcomes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For the second stage of the mediation model (self-esteem→pro-social tendency), self-esteem was positively associated with pro-social tendencies in LBAs. This finding is congruent with previous research (Zuffiano et al, 2016; Fu et al, 2017; McChesney and Toseeb, 2018), indicating that people with high self-esteem are more likely to have high pro-social tendency. This finding supports the notion that self-esteem is a motivating factor and important psychological resource for achieving positive social outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Individuals with low self-esteem may have fewer cognitive resources to cope with daily stressors, making them vulnerable to emotional exhaustion and social maladjustment. Previous studies have demonstrated that low self-esteem was more prevalent among LBAs than non-LABs (Tang et al, 2018) and that self-esteem is positively associated with pro-social tendencies (Yun and Lee, 2007), which indicates that those with high self-esteem are more likely to have pro-social tendencies (Fu et al, 2017; McChesney and Toseeb, 2018). Furthermore, self-esteem is considered to be a mediator between family function and internet addiction (Shi et al, 2017), as well as a mediator between social support/happiness and pro-social tendencies (Guo et al, 2014; McChesney and Toseeb, 2018) in other populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence and severity of ASD traits and social support are two factors shown to be related to well‐being across both ASD and non‐ASD clinical and normative samples. Although children with ASD in the study by McChesney and Toseeb [] showed relatively high levels of positive well‐being, overall levels were lower than for children without ASD. Furthermore, children with ASD who fared worse in terms of positive well‐being had more behavioral, communication, and social problems, suggesting symptom severity may have impacted well‐being.…”
Section: Predictors Of Mental Health and Well‐beingmentioning
confidence: 96%
“…Furthermore, positive well‐being in the typically developing population may foster resilience and buffer against negative mental health and other poor outcomes [Teismann, Brailovskaia, et al, ; Teismann et al, ; Wilhelm, Wedgwood, Parker, Geerligs, & Hadzi‐Pavlovic, ]. However, with the exception of the recent population based study from the United Kingdom which reported that children with ASD exhibit relatively high levels of traits and behaviors indicative of positive well‐being, such as self‐esteem and happiness [McChesney & Toseeb, ], positive well‐being remains understudied in ASD.…”
mentioning
confidence: 99%